THE GROWTH OF RED TILAPIA (Oreochromis sp) IN CONTAINER WHIT DIFFERENT FORMS OF RESIRCULATION SYSTEM - Ramadhani, Ramadhani; Mulyadi, Mulyadi; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT               This research was conducted from April to June 2018 for 42 days at the TIU Improvement (Technical Implementation Unit) Faculty of Fisheries and Marine Science, Riau University. The purpose of this study is to in vestigatedifferent form of container with recirculation systems. Water treatment from tarpaulin with a capacity of 80 L in air volume. Fish stock was 20 fish/tank. The research method was the experimental method with 4 treatments and 3 replications. Treatments was : P1= Circle Shape, P2 = Square Shape, P3= Leg Length and P4= Triangle Shape. The results of this study can be concluded that the different forms of container are not significant to the growth of red tilapia, but the forms of containers are significantly different for the survival of red tilapia. Growth performance of round shape, square shape, rectangular shape and triangle shape, each of which has given weight growth 9.12 g; 10.04 g; 8.95 g; and 8.49 g, then the growth of a double length of 4.30 cm; 4.56 cm; 4.13 cm; and 4.03 cm, daily growth rate of 4.29%, 4.67%, 4.43% and 4.34, feed feed 82,04%, 91,47%, 83,61% and 79,66%, and the rate of life is 85.00%, 96.66%, 90.00% and 85.00%. The measurement results of water quality are still in the optimal range in the maintenance of red tilapia, namely temperatures of 26-29.3 ° C, pH 6.3-6.8, DO 4.5-6.1 mg / L, and ammonia 0.26- 0.17 mg / L.Keywords : Oreochromis sp, recirculation system, different shape of tank survival rate